Application of Chicken Whole Egg Powder in the Manufacture of Bread Compared with using Fresh Egg as Control - Abdi Abdi; Tuty Anggraini; Alfi Asben (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2023)
Whole egg powder has a longer shelf life than fresh eggs, easier to apply, and can be applied in bakery industry. This study aims to evaluate the differences in the characteristics of bread made from chicken whole egg powder dried using the oven and foam mat drying methods compared to bread made from fresh eggs. The results obtained show that bread from chicken whole egg powder dried using the oven drying and foam mat drying methods was liked and accepted by consumers, especially from a sensory perspective (color, aroma, taste and texture), and even has a preference compared to bread made with the use of fresh eggs. The best formulation for bread was obtained from bread made using chicken whole egg powder dried with foam mat drying with color, taste, aroma and texture parameter value are 4.1, 4.3, 3.9 and 4.2 respectively, while the increasing volume was 289.6% and hardness value was 50.8 N/cm2. However, the characteristics of the bread produced using chicken whole egg powder from both the oven drying and foam mat drying methods were not much different from bread made using fresh eggs and can be a new alternative in food industry.